Pengembangan Sistem Informasi Manajemen RT untuk Pengelolaan Data Penduduk dan Pencatatan Aktivitas RT Berbasis Web Menggunakan Metode Waterfall - Dedy Irwan (STMIK Budi Darma, 2023)
RT Management Information System (SIM-RT) is an important tool in the management of information and activities in the RT environment. However, there are still challenges in managing population data and recording RT activity effectively and efficiently. Therefore, the study aims to develop a web-based RT Management Information System that can facilitate the management of population data and the recording of RT activity. The research uses a Waterfall system development approach that includes needs analysis, user interface design, system development, testing, and evaluation. In the development of the system, the focus is on the web platform as the primary media that can be accessed by RT managers and RT citizens through the web browser. Key features noted include population data management such as basic information, marriage status, family data, as well as activity recording such as RT meetings, arisan, and gotong royong activities. Expected with the development of these systems, the management of information and activities in the RT environment can be more efficient and efficient. Users can easily access population data, perform searches and filters, and update information quickly. In addition, RT managers can also easily record and track activities carried out in the RT environment. The system development results were tested using the User Acceptance Test (UAT) method with an average total percentage score of 89%.